Peran Orang Tua dalam Motivasi Belajar Peserta Didik Paket B di SKB Gresik - Azmy, M. Royyan; Yusuf, Ali (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2023)
The purpose of this research is to describe and analyze the role of parents on students' learning motivation. And also describe the learning motivation of students in learning at SKB Gresik. The method used in this research is a qualitative method with the type of field research. The writing method used in this research is a descriptive method that aims to describe the phenomena found in the field, the data collected in this study were collected by means of observation, interviews and documentation, with data analysis using data collection techniques, data reduction, data analysis, data presentation and conclusion drawing. The results obtained in this study indicate that. Parents as the highest authority in the family have an important role in the learning process of children, both directly and indirectly. The role of parents is needed by children to encourage and spur motivation in the child's learning process. With attention in the child's learning process in the form of parental involvement.